E-025 First Reported Case of Mechanical Thrombectomy for Acute Ischemic Stroke in an Individual with a Total Artificial Heart. (29th July 2016) - Nezhad, M; Eboli, P; Austin, M; Schlick, K; Alexander, M
Abstract : Background: With the results of recent thrombectomy trials, endovascular therapy (EVT) is standard of care in appropriately selected patients with acute ischemic stroke (AIS). We report the first case of mechanical thrombectomy for a patient supported by a total artificial heart (TAH) with AIS. Clinical Presentation: A 37 year old male patient with ischemic cardiomyopathy was found to have right gaze preference, left facial droop, and global aphasia 9 days following implantation of a TAH. Prior to ictus, antithrombotic regimen included daily aspirin and heparin infusion at therapeutic levels. Acute imaging revealed a 6 mm left M2 thrombus with associated perfusion mismatch seen in the left MCA territory along with a smaller matched perfusion defect seen in the right MCA territory. Intervention: Following confirmation of lesion amenable to mechanical thrombectomy, patient underwent successful TICI 3 revascularization of the left MCA territory with a Solitaire stent retriever. Repeat perfusion imaging revealed resolved left MCA territory mismatch with persistent right MCA matched defect. His speech improved to an expressive aphasia following revascularization. Conclusion: EVT has been proven to be safe and efficacious for AIS. Prior reports have demonstrated benefit for patients with concurrent mechanical circulatory support devices; however, our report is the first case demonstrating efficacy with a TAH device. Presence of mechanical circulatory support devices should not exclude EVT in individuals with AIS. Disclosures: M. Nezhad: None. P. Eboli: None. M. Austin: None. K. Schlick: None. M. Alexander: None.